Business Ethics and Organizational Sustainability: A Narrative Study on Economic, Social, and Environmental Dimensions - Maidarfrida, Maidarfrida; Ambrin, Ambrin; Wulandari, Fitri (Institut Muslim Cendekia, 2026)
Business ethics and sustainability are widely recognized as interrelated and essential foundations for long-term corporate resilience. Amidst increasing economic, social, and environmental challenges, the relationship between ethical behavior and sustainable practices is becoming increasingly clear. This study aimed to explore the ethical principles that contributed to economic, social, and environmental sustainability, with a focus on their application in Indonesia. This study employed a narrative literature review approach by synthesizing insights from 50 high-quality journal articles (indexed in Q1 and SINTA 3) published between 2020 and 2025. The results indicated that integrating ethical values with Corporate Social Responsibility (CSR) programs and Environmental, Social, and Governance (ESG) practices were crucial for promoting sustainable business performance. The triple bottom line framework emphasized a balance between economic growth, social justice, and environmental protection. However, challenges included limited infrastructure, high implementation costs, and organizational resistance to change. This study highlighted ethical leadership, digital transformation, and green innovation as key drivers of sustainability, particularly in the context of Indonesia as a developing country. The novelty of this research lay in its integrative method, which simultaneously analyzed business ethics, CSR, and ESG within a single framework of organizational sustainability grounded in the triple bottom line in Indonesia as a developing country.